Association between industrial air pollutant exposure and cysteinyl laukotrienes level among school children in Kemaman, Malaysia - Suhaimi, Nur Faseeha (2016)
Industrial activities contribute to atmospheric pollution either directly or through background concentrations. The effects of industrial air pollution are pernicious especially to children due to their developing respiratory system. Although associations between short term and long term exposure to air pollutants with various health effects have been observed, their connections are complex and difficult to be explained. This study aims to determine the association between industrial air pollutants (PM10, PM2.5, NO2, SO2) exposure on cysteinyl leukotrienes (CysLTs) level among school children in Kemaman district. Secretion of CysLTs as inflammatory mediator was explored in this study to understand the connection between exposure to air pollutants and the concentration of CysLTs secreted to indicate the magnitude of exposure. A crosssectional comparative study was conducted at selected primary schools in Kemaman with respondents chosen among those who fulfilled the inclusion criteria. Exposed schools were determined from those located within 5 km radius from an industrial area, whereas comparative schools were determined from those located more than 5 km radius from an industrial area with less traffic. Questionnaires adapted from American Thoracic Society and International Study of Asthma and Allergies in Childhood were used to determine respiratory symptoms, history of exposure and demographic background. Special equipment were used for exposure monitoring of the air pollutants in schools and residences. CysLTs were measured as biomarker of mediator following inflammation by using ELISA. Comparison between the two areas showed significant differences were found between cough, phlegm and wheezing. Exposed group’s exposures to PM10, PM2.5, SO2 and NO2 in schools and residences were significantly higher than comparative group’s exposures. Exposed group’s CysLTs level was also higher than comparative group’s CysLTs level with significant difference. Cough was revealed to have a significant association with all air pollutants measured in the schools, also SO2 and NO2 in residences. Phlegm was only significantly associated with SO2 in schools, whereas wheezing was significantly associated with PM10, SO2 and NO2 in schools. CysLTs had significant associations with PM10, PM2.5, SO2 and NO2 in schools, also with PM2.5, SO2 and NO2 in residences. Results from Multiple Linear Regression shows that the most significant factors associated with level of CysLTs are SO2 in schools, PM2.5 and NO2 in residences, whereas results from Multiple Logistic Regression shows the most significant predictors of CysLTs concentration are SO2 in schools, PM2.5 in residences, and distance of residences from factory. On the whole, school children exposed to higher concentration of industrial air pollutants may potentially increase their level of CysLTs. The findings provide fundamental aspects relevant to future interventions to healthy children living near an industrial area from the environmental scope